Cyberbullying: práticas e consequências da violência virtual na escola - Ribeiro, Neide Aparecida (2018)
It is a study of cyberbullying, the subject of the Doctoral Program in Education of the Catholic University of Brasilia (UCB), aligned in the Education, Youth and Society research program in the sub-area of "Education in non-formal contexts characterized by social conflicts, complexity social, juvenile delinquency and dependencies. " The objective is to analyze the phenomenon of virtual violence practiced by people covered by the teenagers and young people, in which people covered by anonymity or pseudo-anonymity, use this environment by information that may imply in invasion and violation privacy or intimacy of third parties. The problem is centered on the practices of deliberate acts by users and on the consequences that result in violating the person victim of ridicule, discrimination, prejudice of any nature, exclusion and exposure of privacy on the Internet. The virtual site enables, at a devastating level, information to be transmitted and reproduced instantly, making it difficult for actions that can reduce psychological, physical and material damages to the person who is in these conditions. These are serious questions in which teachers, parents and managers are not prepared to deal with violence that goes beyond the physical space of school. In Brazil, there are no effective public policies to prevent and combat cyberbullying or legal or governmental guidelines that can be applied in school institutions, despite the existence of sparse legislation in the area of criminalization and the incidence of increasingly recurring cases registered on the website SaferNet of victims who suffer from the unauthorized exposure of images or personal information on the Internet. It is justified, therefore, the importance of research by the preventive dimension to be addressed in the schools, through the filtering of social networks and adoption of alternative measures to minimize the risks and damages of virtual violence. In the investigation of the problem will be used methods inspired by the netnography, of Kozinets (2014), that consists of the observation and immersion in online communities, to analyze and to collect data through the application of semi- structured questionnaires. In the face-to-face environment, a documentary analysis of the bills and legislation in force will be carried out between 2012 and 2017, observation and application of semi-structured interviews in four municipal schools in the city of Palmas, Tocantins. The material collected online and offline will be analyzed from the perspective of the discourse analysis of Foucault (1999) and Fairclough (2001 [1992]). The expected results may indicate that young people have inserted private information into the network, sometimes being caught as victims, sometimes being the perpetrators, often without a full notion of the serious consequences that the actions perpetrated can have on the lives of others. Appropriate public policies, contextualized and in line with regional reality, should also be suggested for the qualification of teachers and school administrators in the prevention and coping of cyberbullying.